Performance analysis of WDM MIMO RoFSO links for 5G applications - Tony Jose; Victor Du John; Shanthini Pandiaraj (Universitas Ahmad Dahlan, 2022)
The soon to be deployed 5G systems are expected to cater an agglomerate of services at profuse data rates wirelessly. Radio over fiber (RoF) networks are the most suitable to implement such systems. In situations where the practical implementation of RoF systems are non-viable, radio over free space optical (RoFSO) links can be employed. The traditional wavelength division multiplexing (WDM) technology can be incorporated to multiply the data rates. However, the link performance may be degraded due to various atmospheric factors. This can be compensated using multiple input multiple output (MIMO) techniques. In this paper, the performance analysis of such a WDM RoFSO link for 5G frequencies is carried out. The work also presents quantitative performance comparison between single input single output (SISO) and MIMO RoFSO links for 5G systems which will be useful for researchers in this area. It is observed that, while WDM provides additional data capacity, it degrades the link performance under adverse weather conditions which can be counterbalanced using MIMO techniques.